(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
Experiments are run to show that different machining conditions applied to ultra-fine grained pure titanium lead to different levels of grain coarsening and softening near the machined surface. Under “hard” machining conditions the upper 40 microns of the machined surface are altered with a decreased microhardness. The experimental results are reasonably reproduced by model calculations. Expanding the parameter field of the model calculations, the surface coarsening diagram and the surface softening diagram due to machining are presented, showing the region of technological parameters, under which neither grain coarsening nor softening takes place along the machined surface.